Preschool and Child Development under Extreme Poverty : Evidence from a Randomized Experiment in Rural Mozambique - Martinez, Sebastian (World Bank, Washington, DC, 2017)
This study analyzed the impact of a community-based preschool program on child development and schooling outcomes in high-poverty areas of rural Mozambique. Preschools were randomly assigned to 30 of 76 eligible communities. Using a panel survey of 2,000 households with preschool aged children, the study found that children who attended preschool experienced gains in cognitive development, communication, fine motor skills, and socio-emotional skills, scoring 0.33 standard deviations higher on a child development screening test. Preschoolers were 21 percentage points more likely to be enrolled in primary school, 14.9 percentage points more likely to enroll at the appropriate age, and had higher cognitive and communication scores in first grade. Treatment effects were generally larger for children from vulnerable households, those with higher initial development levels, and those with longer exposure to treatment. The preschool intervention also generated positive spillovers by increasing the school enrollment of older siblings and labor supply of adult caregivers. At a cost of approximately $3 per child per month, community-led preschools have the potential to be a cost-effective policy option for helping children meet their development potential even in the most resource deprived parts of the world.